Cancer Cachexia Induces Preferential Skeletal Muscle Myosin Loss When Combined With Denervation - Yamada, Takashi; Ashida, Yuki; Tatebayashi, Daisuke; Abe, Masami; Himori, Koichi (Frontiers in Physiology, 2020)
Patients with cancer cachexia (CCX) suffer from muscle wasting, which is often but not always accompanied by selective loss of myosin. Here we examined the effects of CCX on muscle mass and myosin heavy chain (MyHC) expression in denervated (DEN) muscles, especially focusing on the protein synthesis and degradation pathways. Male CD2F1 mice were randomly divided into control (CNT) and CCX groups and their left sciatic nerve was transected. CCX was induced by an intraperitoneal injection of colon 26 cells. After 14 days, the serum concentration of IL-6 and corticosteroid was higher in CCX mice than in CNT mice. The combination of CCX with DEN (CCX + DEN) resulted in a marked reduction of the gastrocnemius muscle weight (-69%) that was significantly lower than DEN (-53%) or CCX (-36%) alone. CCX had no effect on MyHC content, but it elicited a preferential MyHC loss when combined with DEN. The expression levels of autophagy markers cathepsin D and LC3BII/I ratio were markedly higher in the CCX + DEN group than in the CNT + DEN and the CCX groups. Paradoxically, there was an increase in protein synthesis rate and phosphorylation levels of p70S6K and rpS6, markers of mTORC1 signalling, in the CNT + DEN group, and these molecular alterations were inhibited in the CCX + DEN group. Our data suggest that CCX aggravates muscle atrophy in DEN muscles by inducing seletive loss of myosin, which involves inactivity dependent mechanisms that is likely to be a consequence of increased autophagy-mediated protein breakdown coupled with impaired protein synthesis.